Advances in botanical-based nanoformulations for sustainable cotton insect pest management in developing countries - Luneja, Renatus Laurent; Mkindi, Angela Gerald (Frontiers in Agronomy, 2025)
Cotton is an important crop that significantly contributes to the economies of developing countries, providing income for farmers and driving economic growth in rural areas. However, cotton production in developing countries faces significant challenges due to insect pest infestations. The main impacts include yield losses and increased reliance on synthetic pesticides. Recent advances in pest management are constrained by the use of chemical pesticides that are harmful to the environment and less efficacy and stability of bio-based formulations, especially plant-based. Challenges are more significant in the developing countries where low technology, and reliance on synthetic adulterated products are experienced. To evaluate advances in sustainable pest management, 760 articles were collated and screened. A total of 39 qualified peer-reviewed articles were used to evaluate current research advancements in botanical nanoformulations for sustainable cotton insect pest management in developing countries and examined their efficacy on key cotton insect pests, formulation techniques, mode of action and environmental impact while identifying challenges such as nanoparticle stability and scalability. Results showed that botanical nanoformulations such as silver and zinc nanoparticles, nano-emulsions, and polymeric carriers enhance efficacy, stability, and environmental sustainability. About 85% of the studies were laboratory-based experiments, with only 15% being semi-field and/or field trials. Findings indicate that botanical nanoformulations are viable alternative for manging cotton insect pest management. However more researches are needed to optimize their stability and efficacy in real-world cotton insect pest management in developing countries context.